Identifying the dominant seasonal drivers of land surface temperature on Xiamen Island: an urban functional zone perspective - Xu, Yaolu (Frontiers in Environmental Science, 2025)
Rapid global urbanization has reshaped urban morphology and intensified environmental challenges, while research on factors influencing land surface temperature (LST) in island cities remains limited. We investigated seasonal variations in LST across four urban functional zones (UFZs) on Xiamen Island, China—residential blocks (RBs), public administration and public service blocks (PABs), commercial and business service blocks (CBSBs), and warehouse and storage blocks (WSBs)—using multiple stepwise regression to analyze 18 natural and anthropogenic factors for their seasonal effects on LST. Natural and anthropogenic factors influenced LST across all seasons, with higher explanatory power in spring and summer (R2 > 0.6 for RBs and WSBs) but lower in winter across most UFZs (R2 ≈ 0.22–0.46). For RBs, LST was primarily influenced by the Y coordinate, with higher temperatures in northern areas, and by anthropogenic factors such as building density (BD) and population density (PD). In PABs, LST was mainly driven by the Y coordinate and PD. The Y coordinate, BD, floor area ratio, and PD influenced CBSBs. WSBs showed strong urban heat island effects, mainly driven by the Y coordinate and PD, while landscape diversity reduced these effects in warehouse blocks. These findings suggest that urban planning should adopt seasonally adaptive, land-use-specific strategies aligned with the thermal response characteristics of different UFZs to enhance heat mitigation and environmental quality.